Burden and Patterns of Multimorbidity: Impact on Disablement in Older Adults. (May 2020) - Jacob, Mini E.; Ni, Pengsheng; Driver, Jane; Leritz, Elizabeth; Leveille, Suzanne G.; Jette, Alan M.; Bean, Jonathan F.
Abstract : Objective: The aim of this study was to assess the impact of the burden and patterns of multimorbidity on disability domains. Design: In a cross-sectional study of 425 older adults from the Boston Rehabilitative Impairment Study of the Elderly, participants self-reported 13 chronic conditions and underwent assessment of body function (leg strength, velocity, and power, trunk extensor endurance, leg range of motion, foot sensation), activities (400-m walk test, Short Physical Performance Battery, Late Life Function and Disability Instrument function scores) and participation (Late Life Function and Disability Instrument participation scores). The association between multimorbidity patterns (identified by latent class analysis) and disablement measures, as well as multimorbidity burden (captured by a multimorbidity score) and disablement measures, was tested. Results: Latent class analysis identified three classes—low multimorbidity, high multimorbidity, and predominantly musculoskeletal conditions. Class membership (multimorbidity pattern) was not associated with disablement measures, but multimorbidity score was associated with poor performance in all domains. A 1-point higher multimorbidity score was associated with lower scores in body functions (by 0.06 SD unit), activities (0.07–0.10 SD units), as well as participation (0.07–0.09 units). Conclusion: Multimorbidity counts may be an excellent tool for risk stratification and identification of persons in need of rehabilitation. To Claim CME Credits: Complete the self-assessment activity and evaluation online at http://www.physiatry.org/JournalCME CME Objectives: Upon completion of this article, the reader should be able to (1) describe and distinguish the effect of multimorbidity burden and multimorbidity patterns on three disability domains in older adults; (2) identify and discuss possible reasons why high multimorbidity burden may result in a restriction among social participation in older adults; and (3) detect disability risk among older patients during clinical assessment by using a simple count of common chronic conditions. Level: Advanced Accreditation: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians. The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 1.0 AMA PRA Category 1 Credit(s) ™. Physicians should only claim credit commensurate with the extent of their participation in the activity. Abstract : Supplemental digital content is available in the text.